The Effect of High School Sports Participation on the Use of Performance-Enhancing Substances in Young Adulthood - Dodge, Tonya L.; Jaccard, James J. (Journal of adolescent health, 2006)
The present study examined the relationship between high school sports participation and the use of anabolic steroids (AS) and legal performance-enhancing dietary supplements in young adulthood. Additionally, the relationship between the use of AS and legal dietary supplements was explored. Data on approximately 15,000 adolescents from the National Longitudinal Study of Adolescent Health were used. School sports participation was assessed when adolescents were in grades 7–12. AS use and legal performance-enhancing dietary supplement use were assessed six years later. Males were more likely than females to use AS and legal supplements. A sport by gender interaction emerged for the use of AS, indicating that the gender differences in AS use were greater for those who participated in sports during high school. High school sports participation was associated with increased likelihood that adolescents would use legal supplements in young adulthood. Finally, there was a positive relationship between the use of legal dietary supplements and AS use. This study highlights the important role that the social environment during adolescence has on future health behaviors. Results suggest that the sporting context experienced during early adolescence may have lasting effects on the use of performance-enhancing substances. The use of legal performance-enhancing dietary supplements appears to be more prevalent than the use of AS, and there seems to be a positive relationship between the use of AS and legal performance-enhancing dietary supplements.